ЕВРАЗИЙСКАЯ ИДЕОЛОГИЯ И ТЮРКСКИЕ ИСТОРИЧЕСКИЕ МИФЫ: ГЕОПОЛИТИЧЕСКИЙ КОНТЕКСТ - КРЮЧКОВ, ДМИТРИЙ (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В данной статье говорится о таком феномене ХХ века, как евразийскаяидеология. Проводится анализ евразийства, рассматривается история этого движения,начиная с зарождения в 20-х годах ХХ века, его развития в середине ХХ века в трудахГумилева и заканчивая современностью, в которой евразийство стало полноценнойгосударственной идеологией, используемой различными странами постсоветскогопространства. Описывается и анализируется современная ситуация в государствахевразийского региона, которые так или иначе используют эту идеологию для различныхвнутреннеполитических и внешнеполитических целей.Крючков Дмитро ЄВРАЗІЙСЬКА ІДЕОЛОГІЯ І ТЮРКСЬКІ ІСТОРИЧНІ МІФИ:ГЕОПОЛІТИЧНИЙ КОНТЕКСТ У даній статті йдеться про такий феномен ХХстоліття, як євразійська ідеологія. Проводиться аналіз євразійства, розглядаєтьсяісторія цього руху, починаючи з зародження в 20-х роках ХХ століття, його розвитку всередині ХХ століття в працях Гумільова і закінчуючи сучасністю, в якій євразійствостало повноцінною державною ідеологією, використовуваної різними країнамипострадянського простору. Описується та аналізується сучасна ситуація в державахєвразійського регіону, які так чи інакше використовують цю ідеологію для різнихвнутрішньополітичних і зовнішньополітичних цілей.Ключові слова: Євразія, євразійство, геополітика, тюрки.Dmitry Kriuchkov EURASIAN TURKIC IDEOLOGY AND HISTORICAL MYTHS: THEGEOPOLITICAL CONTEXT The purpose of this article is to analyze and find the relationshipbetween the Turkic historical myths and ideology of the pre-Soviet, Soviet and post-SovietEurasian contemporary culture in Russia, Kazakhstan and neighboring states. Eurasianism, anideology, can rightly be considered one of the ways of further development of the geopoliticalregion in general, and each country in particular, making it a priority to study and necessary.Thus, it is necessary to analyze the development of Eurasian concept from Russianimmigrants, among whom Eurasianism was born as a movement with ideological components,trace the role played in the Eurasian doctrine Gumilev, how Gumilev proves the uniqueness ofthe region and its unique culturally based his theory of ethnogenesis by synthesis Slavic andTurkic peoples.Also, it is important to fully consider and evaluate the role of the modern ideology ofEurasianism as early as twenty-first century, in such powerful Eurasian countries as Russia andKazakhstan that claim to leadership in the region, note the role played by ideology in bothcountries.We clearly see that Eurasianism, an ideology, is now used by various States toperform certain tasks and solve certain issues, such as an internal nature and external. ForRussia, Eurasianism was a way justify the uniqueness of their own culture, a particular ideology,which can be used as a basis for national and state development in the future. For Kazakhstan,as a state that gained independence only recently, Eurasianism - a kind of way to the West, exitto the west field and geopolitical space. Thanks Eurasianism Kazakh politicians can unitediverse population of the state around one idea, profitable as in the field of foreign policy anddomestic. For the Tatar people, Eurasianism is one way to justify its claim to independence.It is also important to consider the impact of Eurasianism and the contemporaryUkraine and Ukrainian culture, because, being directly part of Eurasia, we also face ageopolitical choice between East and West.Keywords: Euroasia, Euroasian ideology, geopolitics, the Turkish nations.